Report For The Business Plan Business Name: Dressmaker (Amaryllis Couture) / Nur Anis Umairah Ahmad Shukor - Ahmad Shukor, Nur Anis Umairah (2020)
Amaryllis Couture is a business that can be categorized as a Small Medium Enterprise (SME) which provide tailoring service to the customer. Amaryllis Couture are specialized in clothes designing as we produce made to measure custom clothing for middle class women , modern wearer and so on. I also believe that it is the main element that could attract a person eye, especially women. Amaryllis Couture consists of two business partnership who contribute same amount of capital and will hold different task and responsibilities in order to manage our business.